Altricial brains and the evolution of infant vocal learning - Renata B. Biazzi; Daniel Y. Takahashi; Asif A. Ghazanfar (Proceedings of the National Academy of Sciences, 2025)
Vocal development in human infants is strongly influenced by interactions with caregivers who reinforce more speech-like sounds. This trajectory of vocal development in humans is radically different from those of our close phylogenetic relatives, cercopithecoid monkeys and apes. In these primates, social feedback seems to play no significant role in their vocal development. Oddly,marmoset monkeys, a more distantly related primate species, do exhibit socially guided vocal learning. How can this be? We hypothesized that the evolution of human and marmoset vocal learning in early infancy is facilitated by their neurally altricial births (relative to other primates) and their cooperative breeding social environment. Our analysis found that, indeed, both human and marmoset brains are growing faster at birth when compared with chimpanzees and rhesus macaques, making humans and marmoset monkeys altricial relative to these other primates. The time interval of this faster brain growth overlaps with important vocal learning milestones. We formalized our hypothesis using a simple model showing that if vocal learning is influenced by the timing of brain growth and social stimuli, it benefits from an altricial brain and a cooperative breeding environment. Our data support the idea that the evolution of socially guided vocal learning during early infancy in humans and marmosets was afforded by infants with an altricial brain embedded in a vocally rich environment.